Dimensions of Organizational Strategy - Hasibuan, Fitriyani; Isa Indrawan, Muhammad (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
BPJS Employment has functions and responsibilities such as, carrying out and receiving registration for BPJS participants, collecting and collecting contributions from participants and employers, receiving contribution assistance from the government, managing social security funds for the benefit of participants, collecting and managing data on social security program participants, provide benefits and financial health services in accordance with the provisions of the social security program, and is also responsible for providing information regarding the implementation of the social security program to participants and the community. This research aims to see the influence of work discipline and work motivation on organizational strategies mediated by work supervision at BPJS Employment throughout Medan Raya. The results of this research are as follows; Work Discipline has a positive and significant effect on Work Supervision with an original sample value of 0.646 and ap value of 0.000. Work Discipline has a positive and significant effect on Organizational Strategy with an original sample value of 0.348 and ap value of 0.000. Work Motivation has a positive and significant effect on Work Supervision with an original sample value of 0.298 and ap value of 0.000. Work Motivation has a positive and insignificant effect on Organizational Strategy with an original sample value of 0.090 and ap value of 0.209. Work Supervision has a positive and significant effect on Organizational Strategy with an original sample value of 0.508 and ap value of 0.000. Work Discipline has a positive and significant effect on Organizational Strategy through Work Supervision with an original sample value of 0.328 and ap value of 0.000. Work Motivation has a positive and significant effect on Organizational Strategy through Work Supervision with an original sample value of 0.151 and ap value of 0.000.